THU0058 B CELL SYNOVITIS AND CLINICAL PHENOTYPES IN RHEUMATOID ARTHRITIS AT DIFFERENT DISEASE STAGES. (June 2019) - Rivellese, Felice; Humby, Frances; Bugatti, Serena; Fossati-Jimack, Liliane; Rizvi, Hasan; Lucchesi, Davide; Ribera, Gloria Lliso; Nerviani, Alessandra; Hands, Rebecca; Giorli, Giovanni; Frias, Barbara; Jaworska, Edyta; et al.
Abstract : Background: The role of B cells in the pathogenesis of Rheumatoid Arthritis (RA) is well recognised and has been reinforced by the established efficacy of B cell depleting treatments. However, B cell infiltration in synovia is highly variable and their association with clinical disease activity has been inconsistently reported, with contradicting results possibly linked to the lack of standardization in quantitative and qualitative assessment of B cell synovitis. In particular, the presence of B cells in synovia has never been systematically assessed in large cohorts. Objectives: To evaluate B cells and their association with clinical phenotypes in the synovia of patients with RA at various disease stages. Methods: A total of 432 synovial biopsies from the following cohorts of RA patients were analysed: i. early (<1 year) treatment-naïve RA (n=165), ii. Synthetic Disease Modifying Anti-Rheumatic Drugs inadequate responders (sDMARDs-ir) (n=103), iii. TNF-inhibitors inadequate responders (TNFi-ir) (n=164). Haematoxylin and eosin staining was used for the assessment of synovitis according to a previously validated score (Krenn). Upon immunohistochemical staining for CD20, semi-quantitative (Sq) scoring (0-4) was used to classify patients into B cell rich (≥ 2) and poor (< 2) and automated digital image analysis (DIA) to calculate the B cell area fraction. B cell expression markers, including CD20 mRNA counts and a composite B cell module, were obtained by RNA-sequencing from early RA synovial biopsies (n=91). Results: Semi-quantitative synovial B cell scores positively correlated with the B cell area fraction obtained by DIA (Spearman r 0.93 in early RA and 0.88 in TNFi-ir, p<0.0001). Accordingly, B cell rich patients (Sq score ≥ 2) had a significantly higher B cell area fraction (p<0.0001). RNA-sequencing from 91 patients with early RA showed a positive correlation between the Sq B cell scores and CD20 mRNA counts and the B cell module (Spearman r=0.6 and 0.67, respectively, p<0.0001). Similarly, a positive correlation was found between the B cell area fraction obtained by DIA and CD20 mRNA counts and B cell module (r=0.67 and 0.69, respectively, p<0.0001) When comparing B cell presence in the three cohorts, B cell-rich synovitis was present in 35% of early RA, 36% of sDMARDs-ir and 47.1% of TNFi-ir (p=0.025 comparing early RA vs late-stage TNFi-ir patients). Finally, while B cell-rich patients showed significantly higher synovial inflammatory scores across all cohorts, higher disease activity (number of swollen joints, DAS28) and higher prevalence of autoantibody positivity (ACPA and RF) in B cell-rich patients were observed exclusively in the early RA cohort. Conclusion: We here describe a robust and validated synovial B cell score that can potentially contribute to patient stratification in RA, as it helps identifying an enrichment of B cell synovitis in established disease, uncoupled from clinical disease activity. Acknowledgement: We would like to thank all the investigators and recruitment centers from PEAC (http://www.peac-mrc.mds.qmul.ac.uk/centres.php), STRAP (http://www.matura-mrc.whri.qmul.ac.uk/strap_recruiting_centers.php) and R4RA (http://www.r4ra-nihr.whri.qmul.ac.uk/recruiting_centres.php) and the EMR clinical trial team at Queen Mary (http://www.r4ra-nihr.whri.qmul.ac.uk/docs/contributors_r4ra-for_website.pdf) Disclosure of Interests: Felice Rivellese: None declared, Frances Humby: None declared, Serena Bugatti Speakers bureau: Bristol-Myers Squibb, Celgene, Lilly, Novartis, Sanofi, Janssen, Liliane Fossati-Jimack: None declared, Hasan Rizvi: None declared, Davide Lucchesi: None declared, Gloria Lliso Ribera: None declared, Alessandra Nerviani: None declared, Rebecca Hands: None declared, Giovanni Giorli: None declared, Barbara Frias: None declared, Edyta Jaworska: None declared, Katriona Goldmann: None declared, Myles Lewis Grant/research support from: Celgene, Antonio Manzo: None declared, Michele Bombardieri Grant/research support from: Celgene, Consultant for: Medimmune, Costantino Pitzalis Grant/research support from: Celgene